Use of the NAL-AB Wordlists as a South African English Speech Discrimination Test - Wayne J. Wilson; Beverley Jones; Peter Fridjhon (South African Journal of Communication Disorders, 1998)
South Africa still lacks a South African English specific speech discrimination test. As an alternative, this study investigated the use of the Australian English, National Acoustic Laboratories Arthur Boothroyd (N AL-AB) wordlists to assess the speech discrimination of South African English speakers. Thirty South African English speakers were tested at 0, 5, 10, 20 and 25 dBHL  (audiometer dial reading) and their performance-intensity functions were compared qualitatively to the NAL-AB wordlist normative data. Results showed three general patterns; similar performance for both groups; poorer performance by the South African English speakers at the low to mid presentation intensities only; and poorer performance by the South African English speakers across most presentation intensities. Use of the NAL-AB wordlists at threshold levels or for site of lesion assessment was therefore concluded to be unwise. Use of these wordlists at supra-threshold levels, however, would provide a valid and reliable option for the speech discrimination assessment of South African English speakers.